Teachers’ Efforts in Improving Students Learning Outcomes Through Evaluation of Class 4 Islamic Religious Education Learning Processes at SD 12 Negeri Simpang Teritip - Saiwanto, Saiwanto; Romelah, Romelah (Journal Transformation of Mandalika, e-ISSN: 2745-5882, p-ISSN: 2962-2956, 2020)
Islamic education is an important part as one of the disciplines in schools where it plays a role in character and personality development. It takes proper learning so that Islamic religious education can really be applied correctly by students. This study was conducted to see how the learning process that is considered appropriate in improving the learning outcomes of grade 4 students at SD 12 Negeri Simpang Teritip through evaluation of the learning process of Islamic education. To find an evaluation of the learning process of Islamic education that is considered appropriate to be applied by collecting literature studies from previous studies. The method used in this study is qualitative where the data are in the form of words and text, both from interviews, observations, and articles or journals from previous studies. The results of this study found that there was still confusion with the results of the evaluation of the Islamic Religious Education learning process in Grade 4 SD 12 Negeri Simpang Teritip. Meanwhile, previous studies were reviewed which could assist in carrying out the evaluation of the learning process more correctly, with the results: (1) in conducting the evaluation there must be validity, effectiveness, different points, and objectivity which are easy to do and not difficult; (2) teachers must change according to the challenges of the times and also want to learn to understand evaluation correctly; and (3) teachers in an effort to improve student learning outcomes must also be willing to improve themselves by adding information and developing self-ability.